PENGEMBANGAN MODUL ELEKTRONIK MENGGUNAKAN APLIKASI KVISOFT FLIPBOOK MAKER PADA MATERI GERAK LURUS KELAS X SMA - Jannah, Miftahul; Islami, Nur; M. Nasir, M. Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The development of Science and Technology has led the world to the 4.0 industrial revolution which requires a teacher to be able to keep up with the times. In addition, there is a lack of use of innovative and attractive learning media for students, so it is necessary to develop practical and attractive teaching materials using certain software. One of the teaching materials that can be developed is an electronic module. This study aims to develop teaching materials in the form of electronic modules using the Kvisoft FlipBook Maker application on Straight Motion material for class X SMA. The type of research used is Research and Development (R&D) using the modified ADDIE model consisting of only 3 stages, namely the analysis, design and development stages. The types of data to be obtained in this research are quantitative data and qualitative data. Quantitative data is in the form of the validity value of the electronic module, and qualitative data is obtained from criticism and suggestions from the validator. The data collection instrument used was in the form of an electronic module validation sheet. Data were analyzed descriptively to determine the validity of the electronic module using the Aiken's V formula. The results showed that the overall validity of the electronic module was valid with an Aiken validity index of 0.87. So that the electronic module using the Kvisoft FlipBook Maker application on Straight Motion material for class X SMA is declared valid based on appearance aspects, software utilization aspects, content feasibility aspects, presentation feasibility aspects, and language feasibility aspects. Key Words: Electronic Module, Kvisoft FlipBook Maker, Straight Motion